From apartheid to Batho Pele: an exploratory study on service delivery and public participation in Atteridgeville-Saulsville - Mulaudzi, Mbulaheni; Liebenberg, Ian (Faculty of Humanities, University of the Free State, 2013)
The focus of the case study is public participation in the local government arena. The article examines the importance of public participation in the policy process and service delivery in Atteridgeville- Saulsville from apartheid times to post-apartheid rule. As a case study, public participation in the Tshwane Metropolitan Council (previously Pretoria City Council or Stadsraad) is traced back to the establishment of this “black township” (a black location in apartheid jargon) and investigated up until 2008. Public participation during the apartheid era was based on racial division. Black people were not allowed to participate in the decision-making processes that affected their locality. Democratic government since 1994, and more so since the acceptance of the democratic constitution, Act 108 of 1996, brought about an emphasis on equal citizen participation regardless of colour, status or geographical location. The Constitution enforces the responsibility of local government to ensure public participation in decision making. In democracies local government structures are traditionally seen as government closest to the people. The term batho pele strongly implies quality service delivery to human communities as well as accountability and transparency with a “human touch”. Service provision should be informed by the needs and aspirations of the local communities, extracted from the community through participation. Making use of a qualitative approach, among others face-to-face interviews, the authors explore the case under review and how those who experience local government view the service delivery flowing from current policy and practice in contrast to that of the past.
Keywords: Local government; Blockman; Service delivery; Public participation; Tshwane Metropolitan Council; Location(s); Bantu Administration; Batho Pele